CRIMINALIZATION OF UNLAWFUL ACTS DOES NOT DETERMINE THE STATUS OF NARCOTIC CONFISCATED GOODS AND NARCOTIC PRECURSORS FOR THE PURPOSE OF PROVING CASES - Amalo, Yandres Junius; Muchtar, Syamsuddin (Universitas Islam Negeri Alauddin Makassar, 2023)
One of the areas of law in carrying out the duties of the Prosecutor's Office according to Article 30 paragraph (1) letter b of the Prosecutor's Law states that the prosecutor's office carries out prosecutions and executors of court decisions that have permanent legal force related to the crime of Narcotics Law Number 35 of 2009 concerning Narcotics (abbreviated Narcotics Law). In this regard, Article 141 of Law number 35 of 2009 concerning Narcotics states that the Head of the District Attorney who unlawfully does not implement the provisions referred to in Article 91 paragraph (1) may be punished. Determination of Sanctions in a criminal law is not merely a matter of mere technical legislation, but is an integral part of the substance or material of the law itself. So that the imposition of sanctions is not necessarily enforced based on the sound of the article but must pay attention to other aspects contained in the regulation, in this case must pay attention to the principles of applicable law. This research is normative legal research by combining conceptual approaches, statutory approaches and case approaches. The results of the research show that the issues of penalization, depenalization, criminalization and decriminalization must be understood comprehensively with all aspects of issues of substance or statutory material at the stage of legislation policy. Based on this concept, care must be taken so that criminalization remains in the correct corridor, namely paying attention to the principles of criminalization (the principle of legality, the principle of subsidiarity, and the principle of equality/equality).